Thursday

March 5, 2015

March 5, 2015

Posted by **noonie** on Friday, April 29, 2011 at 4:55pm.

- algebra -
**Damon**, Friday, April 29, 2011 at 5:08pmsolve the first equation for x

2x = -3y - 5

x = -(3 y/2 +5/2)

substitute in the second

-3(3y/2+5/2) +5y = -9

-9y/2 -15/2 + 10y/2 = -18/2

y = -3

then x = 9y/2 -5/2 = 2

check by using that x and y in equation 1

2x+3y=-5

2*2 + 3*-3 = -5?

4-9 = -5

Yes, checks

**Answer this Question**

**Related Questions**

Algebra II - Use synthetic substitution to find f(-3) for f(x) = 2x^3 - 6x^2 - ...

Algebra help - Match the equation 4x^6-2x^3+1=0. With a substitution from the ...

Algebra help - Match the equation 4x^6-2x^3+1=0. With a substitution from the ...

algebra - i need help with these problems (either a solution or how to plug them...

algebra - use the Substitution Method. Please give it a try. y = 3x + 4 5x + 3y...

chemistry - What will be the fastest reaction if a strong base, such as sodamide...

Calculus 2 - Evalute the integral of x/(x^2+4)dx using u-substitution and then ...

Algebra - Solve: 3x-2y=10 2x+3y=-2 Graph: Substitution: Elimination: Show Your ...

Algebra 1 - bobpursey, In this problem you helped me with earlier: Solve using ...

Trigonometric Substitution - Trigonometric Substitution a. Explain why the ...